ANALISIS GAYA KEPEMIMPINAN PATERNALISTIK DALAM MENINGKATKAN EFEKTIVITAS KERJA KARYAWAN PADA GENZIA DENTAL CARE SANGATTA - Tisa Tandi Datu, Pebriani; Amransyah, Amransyah; Prihatiningsih, Endang (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
This study aims to describe how the paternalistic leadership style is analyzed in improving employee work effectiveness at Genzia Dental Care Sangatta and the impact of this leadership style on enhancing employee performance. This research is a case study and field research, using a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. The results show that the paternalistic leadership style at Genzia Dental Care Sangatta incorporates benevolent and morale leadership aspects. This is evident from various indicators, such as requiring employees to follow procedures and standards, involving them in decision-making, accepting criticism and suggestions, showing concern for employees' personal lives, maintaining formal and informal relationships with employees, providing attention and guidance to underperforming employees, offering better working conditions, treating all employees fairly, and respecting differing opinions. Although many of these indicators are well-implemented, there is still a lack of strictness in enforcing rules, which leads to frequent rule violations by employees